Level of Genetic Diversity in European Bumblebees is Not Determined by Local Species Abundance - Maebe, Kevin; Karise, Reet; Meeus, Ivan; Mänd, Marika; Smagghe, Guy (Frontiers in Genetics, 2019)
Bumblebee species with declining population trends tend to show lower genetic diversity levels than stable species. The observed difference might be explained by abundance differences, with declining bumblebee species having lower genetic diversity levels simply due to their lower local species abundances. However, whether this holds true is not known. Here, we investigated whether bumblebee local abundances determines population genetic diversity levels. Therefore, local species abundances were measured for bumblebee species at four locations in Belgium and two locations in Estonia during bumblebee foraging years 2013-2017. These locations and countries were chosen to ensure the greatest possible variance in both local abundances and population trends for these species. Hence, genetic diversity levels were obtained for seven species by genotyping collected specimens with 16 microsatellites. Our results showed that the observed patterns in genetic diversity did not depend on local species abundance. So, although declining bumblebee species can become locally abundant, they will still show lower genetic diversity levels than stable species. This result implies that measuring bumblebees’ local abundance cannot be used to directly determine the health status of a population. Furthermore, this result has also major impact on future conservation strategies as increasing the genetic diversity levels of declining species will be very difficult, and habitat quality should be high to maintain their populations, otherwise these species are doomed to disappear first.